Suvorexant, an orexin/hypocretin receptor antagonist, attenuates motivational and hedonic properties of cocaine. (17th April 2017) - Gentile, Taylor A.; Simmons, Steven J.; Barker, David J.; Shaw, Jessica K.; España, Rodrigo A.; Muschamp, John W.
Abstract: Orexins ('hypocretins') are peptides produced by neurons of the hypothalamus that project to structures implicated in reward and emotion processing. Converging evidence demonstrates functional roles of orexin signaling in arousal, sleep/wakefulness and motivated behaviors for natural and drug rewards. Suvorexant, a dual orexin receptor antagonist, recently received approval from the US Food and Drug Administration to treat insomnia. In Experiment 1, rats self‐administered cocaine under a progressive‐ratio schedule of reinforcement and the effects of suvorexant on motivation to self‐administer cocaine were measured. In Experiment 2, the effects of suvorexant on cocaine reward were assessed by using a place conditioning paradigm, and 50‐kHz ultrasonic vocalizations were also recorded to track changes in hedonic reactivity to cocaine. To rule out potentially confounding effects of suvorexant‐induced somnolence, locomotor activity was also measured. In Experiment 3, the effects of suvorexant on cocaine‐evoked elevations in ventral striatal dopamine were examined. Data reveal that suvorexant (i) reduced the number of cocaine infusions earned during progressive‐ratio self‐administration; (ii) attenuated initial positive hedonic reactivity to cocaine and prevented cocaine place preference; (iii) did not affect cocaine‐induced hyperlocomotion and (iv) reduced cocaine‐induced elevations in extracellular ventral striatal dopamine. The present study examined the therapeutic potential of suvorexant in rodent models of cocaine use disorder. These results contribute toward a growing literature supporting therapeutic roles of orexin receptor antagonists in treating substance use disorders. Abstract : Our experiments found that suvorexant, the first‐in‐class clinically available dual hypocretin/receptor antagonist, reduces cocaine‐seeking motivation in rats. Additionally, suvorexant was found to augment hedonic reactivity to systemically injected cocaine and attenuate cocaine‐elicited elevations in ventral striatal dopamine release. Collectively, these findings contribute to developing literature positioning hypocretin/orexin receptor antagonists as possible adjunct therapies for treating substance use disorders in humans.